The Concept of Blockchain-Based Triple Entry Accounting in Indonesia - Nugraha, Farhani; Sasongko, Ananta (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
The business world, especially accounting and financial reporting, is experiencing disruptions due to a new technology called blockchain. By using blockchain technology in business, important information within the company becomes well integrated. However, in Indonesia, the development of blockchain both in concept and practice is still very slow. This paper aims to examine the blockchain-based triple entry accounting concept that exists and is developing in Indonesia using a literature review. As a result, Indonesia can apply blockchain-based triple entry accounting to increase transparency, reduce the level of fraud, and increase tax convenience. So, this paper provides regulation implications so that the government develops standardization of the application of blockchain technology.